Modelling and simulation of driving cycle using simulink - S. K. Arun; I. N. Anida; J. S. Norbakyah; A. R. Salisa (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
Driving cycle is commonly known as the relationship and a series of speed-time profile. The study on this discipline aids vehicle manufacturers in vehicle construction, environmentalists in studying environment quality in proportion with vehicle emissions and traffic engineers to further investigate the behaviour of drivers and the road conditions which assist automotive industry in a better and energy efficient vehicle productions. In order to develop a proper driving cycle for selected routes, information and data based on real-time driving behaviour is important. This research focusses on the modelling of each component and latter designing a conceptual model in Simulink which takes up the data of speed of vehicles in SI unit which is m/s and draws out distance travelled and acceleration of the vehicle together with driving cycle of the route for given timestamp. This relation will be verified with existing Kuala Terengganu BasKITe driving cycle, highway fuel economy test (HWFET), new europian driving cycle (NEDC) and worldwide harmonised light vehicle test procedure (WLTP) driving cycles for the use of future projects and improvements of technology in studies and analysis of powertrain and electric vehicle performances.